Rams [videorecording (DVD)] - Neill, Sam; Caton, Michael, 1943-; Richardson, Miranda; Keddie, Asher, 1974- (Samuel Goldwyn Films, 2020)
Two estranged brothers, Colin and Les, are at war raising separate flocks of sheep both descended from the family's bloodline. When Les's prize ram is diagnosed with a rare and lethal illness, authorities order a purge of every sheep in the valley but Colin attempts to stealthily outwit the powers that be.